Factores asociados con riesgo de suicidio de adolescentes y jóvenes autoidentificados como lesbianas, gays y bisexuales: estado actual de la literatura (2013)
Introduction A framework within sexual and reproductive health is presented to understand the mental health issues of the population of lesbian, gay and bisexual (LGB) adolescents and young people. Different ways of understanding the nature of internalized homophobia were developed. On the other hand, in suicidology studies it is understood that the risk of suicide consists of the steps of ideation, planning and attempted suicide, and that there is an increased risk of suicide in the LGB population. Numerous factors have been associated with suicide risk in this population, one of the main internalized homophobia and other mental health problems. Objectives By means of a literature review, to establish the possible relationship between internalized homophobia and ideation and attempted suicide in the LGB population, as well as to identify the mental health problems associated to suicide risk in sexually diverse communities. Method Articles in English and Spanish, mainly within the last five years, were reviewed. They included articles in peer reviewed journals, and databases, such as Google Scholar, Redalyc, Byreme, Ovid, Science Direct, Taylor and Francis, MEDLINE, Scopus, PsycINFO, and Ebsco. Results It was found in the available literature that internalized homophobia is associated with suicide ideation and attempts in adults. A state of science of the major mental health problems associated with suicide risk in young LGB people reported contradictory findings. While some studies showed an association between depression, anxiety and distress and suicidal ideation and attempts, in others, the data do not allow such a conclusion. The theoretical framework presents the most important conceptualizations of suicide risk and emphasizes the social type. It identifies issues of suicide prevention, protective factors that contribute towards this, as well as elements of psychotherapy for LGB consultants. Conclusions It concludes and discusses the importance of studying the sexually diverse as regards determining factors of mental health in Latin America, given the limited amount of literature found in the Spanish language, and myths of major disease that persist in many segments of the population. This review considers it necessary to overcome such contradictions, in order to inform the general population and avoid further stigmatization. © 2012 Asociacion Colombiana de Psiquiatrna.